Beneficial effect of reperfusion therapy beyond the preservation of left ventricular function in patients with acute ST-segment elevation myocardial infarction - Zeymer, Uwe; Bauer, Timm; Gersh, Bernard J.; Zahn, Ralf; Gitt, Anselm Kai; Jünger, Claus Heinrich; Senges, Jochen (International journal of cardiology, 2011)
Background - Reperfusion therapy has been shown to improve mortality in patients with acute ST-segment elevation myocardial infarction. However, in randomized clinical trials there was only a modest improvement in left ventricular ejection fraction with reperfusion therapy, despite a larger improvement in mortality. - Methods - In the prospective MITRA-Plus registry we compared 1-year mortality of inhospital survivors of ST-segment elevation myocardial infarction (STEMI) divided into nine groups with preserved (>55%), moderately reduced (41-55%) and severely reduced (≤40%) left ventricular ejection fraction (LVEF) and treated with no early reperfusion therapy, fibrinolysis or primary percutaneous coronary intervention (PCI) within 24h after admission. - Results - A total of 5867 patients were included in this analysis, 1026 (18%) without early reperfusion, 2462 (42%) with fibrinolysis and 2379 (40%) with primary PCI. After adjustment for confounding variables in a propensity score analysis, reperfusion therapy (Odds ratio and 95% CI: 0.27, 0.15-0.48; 0.50, 0.32-0.79; 0.64, 0.44-0.93), fibrinolysis (Odds ratio and 95% CI: 0.27, 0.14-0.52; 0.58, 0.35-0.95; 0.60, 0.39-0.93) and primary PCI (Odds ratio and 95% CI: 0.22, 0.11-0.44; 0.34, 0.19-0.59; 0.56, 0.36-0.88) remained independent predictors of survival in comparison to no reperfusion therapy in the patients with preserved, moderately reduced and severely reduced LVEF, respectively. - Conclusions - These results suggest a beneficial effect of early reperfusion therapy beyond the preservation of left ventricular function, however the mechanisms need further study.
Available online: 14 July 2009
Gesehen am 22.12.2022